2018
DOI: 10.1002/anie.201804307
|View full text |Cite
|
Sign up to set email alerts
|

Isonitrile Formation by a Non‐Heme Iron(II)‐Dependent Oxidase/Decarboxylase

Abstract: The electron-rich isonitrile is an important functionality in bioactive natural products, but its biosynthesis has been restricted to the IsnA family of isonitrile synthases. We here provide the first structural and biochemical evidence of an alternative mechanism for isonitrile formation. ScoE, a putative non-heme iron(II)-dependent enzyme from Streptomyces coeruleorubidus, was shown to catalyze the conversion of (R)-3-((carboxymethyl)amino)butanoic acid to (R)-3-isocyanobutanoic acid through an oxidative dec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
81
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(86 citation statements)
references
References 18 publications
5
81
0
Order By: Relevance
“…[2] The second type involves an iron(II) and 2-oxoglutarate (Fe/2OG) dependent enzyme catalyzed decarboxylation-assisted -NC group installation. [3] Analysis of the biosynthetic gene clusters responsible for the Fe/2OG enzyme catalyzed isonitrile formation revealed that the pathway involved in isonitrile-containing peptide production is conserved in pathogenic mycobacteria including Mycobac-terium tuberculosis and M. marinum. Related operons are also found in the phylum of Actinobacteria, including Streptomyces.…”
mentioning
confidence: 99%
“…[2] The second type involves an iron(II) and 2-oxoglutarate (Fe/2OG) dependent enzyme catalyzed decarboxylation-assisted -NC group installation. [3] Analysis of the biosynthetic gene clusters responsible for the Fe/2OG enzyme catalyzed isonitrile formation revealed that the pathway involved in isonitrile-containing peptide production is conserved in pathogenic mycobacteria including Mycobac-terium tuberculosis and M. marinum. Related operons are also found in the phylum of Actinobacteria, including Streptomyces.…”
mentioning
confidence: 99%
“…A few di‐isocyanide lipopeptides from microorganisms are known. Antibiotics SF2369 ( 11 ) and SF2768 ( 12 ) are examples and constitute rare examples of diiocyanides in the microbial world , . Recent discoveries concerning their biosynthesis will be detailed (see section 6).…”
Section: Isonitrile In Nature: a Biochemical Storymentioning
confidence: 99%
“…In the two last years, the biosynthetic pathways to lipopeptide isocyanides have been revealed. It is at the heart of the PKS‐NRPS logic that the formation of the isocyanide functional group occurs in some Actinobacteria including Mycobacterium marinum and Streptomyces coeruleorubidus , . A unique NRPS domain denominated ScoE is responsible within the PKS‐NRPS machinery for an oxidative decarboxylation of glycine (Scheme , see discussion on mechanism below).…”
Section: Isocyanide Lipopeptides: Unusual Isocyanide Formation In mentioning
confidence: 99%
See 2 more Smart Citations